2022
DOI: 10.3390/healthcare10122570
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Spirometry Testing among Patients with Asthma and COPD in German General Practices

Abstract: The goal of this study was to estimate the prevalence of spirometry testing among patients with asthma and chronic obstructive pulmonary disease (COPD) in general practices (GPs) in Germany. This retrospective cross-sectional study was based on data from the Disease Analyzer database (IQVIA), This retrospective cross-sectional study included all patients with at least one confirmed asthma or COPD diagnosis in one of those 50 general practices in Germany between January 2020, and January 2021, as well as at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Also, 75% of current smokers and 70% of former smokers, who are at a greater risk of developing COPD, have never performed PFT (p<0.001). This underutilization of spirometry was also observed in two studies conducted in Germany by Härtel et al [ 40 ] and Heinmüller et al [ 41 ] that reported 27% and 29% spirometry prevalence rate among COPD patients, respectively. Also a previous study conducted in a primary care setting showed a prevalence of annual spirometry use of around 27% in patients with COPD in the United States [ 42 ].…”
Section: Discussionsupporting
confidence: 66%
“…Also, 75% of current smokers and 70% of former smokers, who are at a greater risk of developing COPD, have never performed PFT (p<0.001). This underutilization of spirometry was also observed in two studies conducted in Germany by Härtel et al [ 40 ] and Heinmüller et al [ 41 ] that reported 27% and 29% spirometry prevalence rate among COPD patients, respectively. Also a previous study conducted in a primary care setting showed a prevalence of annual spirometry use of around 27% in patients with COPD in the United States [ 42 ].…”
Section: Discussionsupporting
confidence: 66%